Income risk, coping strategies and safety nets - Stefan Dercon (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
High income risk is part of life in developing countries. Climatic risks, economic fluctuations, but also a large number of individual-specific shocks make these households vulnerable to serious hardship. For example, details are given on the various shocks and events causing serious hardship to rural households in Ethiopia in the last twenty years. Not surprisingly for Ethiopia, climatic events are the most common cause of shocks, but many households suffer from other common or idiosyncratic shocks related to economic policy, labour or livestock. Rural and urban households in developing countries face substantial risk. Households in risky environments have developed sophisticated (ex ante) risk-management and (ex post) risk-coping strategies, including self-insurance via savings and informal insurance mechanisms while formal credit and insurance markets appear to contribute only little to reducing income risk and its consequences. Despite these strategies, vulnerability to poverty linked to risk remains high. In this paper, I focus on the opportunities available to households to use risk-management and risk-coping strategies, and on the constraints on their effectiveness, by reviewing some of the recent literature on savings as insurance, income diversification and smoothing, and informal risk-sharing arrangements. Risk and lumpiness limit the opportunities to use assets as insurance. Entry constraints limit the usefulness of income diversification. Informal risk-sharing only provides limited protection, especially for some of the poor and their sustainability during periods of change is in doubt. Public safety nets are likely to be beneficial, but their impact is at times limited while they may have negative externalities on households not covered by the safety net. The paper also discusses the implications for policy as well as the information requirements to increase our understanding of vulnerability and implement better vulnerability reducing policies. – risk ; consumption smoothing ; risk sharing ; safety nets
Keywords: D80; H55; I38; O16; O17; 330; Haushaltseinkommen; Risiko; Privater Haushalt; Entwicklungsländer